2013
DOI: 10.1016/j.freeradbiomed.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant functions for the hemoglobin β93 cysteine residue in erythrocytes and in the vascular compartment in vivo

Abstract: The β93 Cysteine (β93Cys) residue of hemoglobin is conserved in vertebrates but its function in the red blood cell (RBC) remains unclear. Since this residue is present at concentrations more than two orders of magnitude higher than enzymatic components of the RBC antioxidant network, a role in the scavenging of reactive species was hypothesized. Initial studies utilizing mice that express human hemoglobin with either Cys (B93C) or Ala (B93A) at the β93 positions, demonstrated that loss of the β93Cys did not af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 63 publications
5
43
0
Order By: Relevance
“…The presence of nitrite and NO will also foster the formation of SNO-Hb, in which the thiols on b93 cysteine are S-nitrosated. SNO Hb formation has been shown (198) to play a role in limiting oxidative stress and erythrocyte membrane damage by further supporting the concept that NO in many or all of its bioactive forms can function to maintain RBC homeostasis in the presence of oxidative stress. Furthermore, SNO Hb formation has also been shown to be a significant contributor to the mechanism for hypoxic vasodilation (212).…”
Section: The Interplay Of Reduced Nox Generation and Enhanced Ferryl mentioning
confidence: 65%
See 1 more Smart Citation
“…The presence of nitrite and NO will also foster the formation of SNO-Hb, in which the thiols on b93 cysteine are S-nitrosated. SNO Hb formation has been shown (198) to play a role in limiting oxidative stress and erythrocyte membrane damage by further supporting the concept that NO in many or all of its bioactive forms can function to maintain RBC homeostasis in the presence of oxidative stress. Furthermore, SNO Hb formation has also been shown to be a significant contributor to the mechanism for hypoxic vasodilation (212).…”
Section: The Interplay Of Reduced Nox Generation and Enhanced Ferryl mentioning
confidence: 65%
“…This oxidation is significant, in that the reduced state of these thiols plays a key role in protecting against oxidative stress (198). It is when the b93 Cys are oxidized that Hb alterations occur, including Hb dimer/hemichrome formation, which can disrupt the functional Band 3 protein complex under conditions of oxidative stress (110).…”
Section: Fig 2 Hbe Acts As a Bmentioning
confidence: 99%
“…Hemoglobin molecule has also free SH-groups of Cys [16]. Experimental data have shown the increasing of the level of hemoglobin light scattering, being the most pronounced after rapid freezing (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Recent studies suggested a strong antioxidant effect of lichen extract that could ameliorate oxidative stress (Kosanic & Rankovic, 2011). The effects of antioxidants are pronounced in erythrocytes because these cells have increased amounts of hemoglobin and iron ions and consequently they are under higher oxidative stress (Vitturi et al, 2013). The results obtained in vitro suggest that the membrane fragility increases under oxidative stress conditions for the patient RBCs and the protection effect of antioxidants is due to their antioxidant properties (Moreira et al, 2011).…”
Section: Discussionmentioning
confidence: 98%